Education On Maintaining Eye Health As A Prevention Of Vision Disorders Among Ptpn Xii Employees - Aryani Vindhya Putri; Bragastio Sidharta; Agustya Elya Risnanda; Abdul Muis Mahrus (DokTIn MEDIKA Jurnal Pengabdian Masyarakat, 2026)
Background: The eyes are vital organs for vision in all humans, especially workers. Eye health issues can lead to mild to severe vision complaints that affect workers' productivity. Knowledge and education related to eye health are necessary to enhance workers' awareness. Objective: To improve workers' knowledge about eye health. Methods: Providing education to PTPN XII employees and assessing knowledge before and after the education through questionnaires. Results: The education was conducted in May 2024 for 23 employees, with an average knowledge increase from a score of 52 to 75 after the education. Conclusion: Eye health education effectively improves workers' knowledge about eye health.